Updating North Carolina Corn Yields and Nitrogen Recommendations to Match Current Production Practices and New Hybrids. Issue 1 (18th September 2015) - Rajkovich, Shelby R.; Crozier, Carl R.; Smyth, T. Jot; Crouse, David; Osmond, Deanna L.
Abstract : Corn ( Zea mays L.) nitrogen (N) rate trials conducted in North Carolina over a recent 10‐year time frame (2001–2011) were reviewed to potentially adjust yield goals (realistic yield expectations [RYE]) and their associated N rate recommendations in the North Carolina RYE database. The analyzed trial data provided evidence that corn yields increased by 15, 18, and 31% in the Coastal Plain, Piedmont, and Mountain regions, respectively. To reflect these increases, realistic yield expectations in the database were adjusted upward by 20%. However, linear‐plateau regressions confirmed that the current N rate recommendations in the RYE database were appropriate for obtaining optimum agronomic yields and therefore were not adjusted. While our approach does not permit direct statistical comparison of different tillage methods or crop rotations, long‐term no‐till (>10 years) was the only tillage category with higher measured optimum yields and significantly lower calculated N factors (amount of N applied per unit of yield [lb N bu −1 ] at the optimum N rate) than the standard RYE database values. However, measured yields and optimum N rates between conventional and no‐till (>10 years) were similar. For corn following soybean [ Glycine max (L.) Merr.] rotations (but not corn following corn), mean optimum yield was higher and the value of the N factor was lower than the standard values.